2021
DOI: 10.1038/s41597-020-00793-8
|View full text |Cite
|
Sign up to set email alerts
|

An Indo-Pacific coral spawning database

Abstract: The discovery of multi-species synchronous spawning of scleractinian corals on the Great Barrier Reef in the 1980s stimulated an extraordinary effort to document spawning times in other parts of the globe. Unfortunately, most of these data remain unpublished which limits our understanding of regional and global reproductive patterns. The Coral Spawning Database (CSD) collates much of these disparate data into a single place. The CSD includes 6178 observations (3085 of which were unpublished) of the time or day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 97 publications
2
37
0
Order By: Relevance
“…Nonetheless, expanding the representation of coral reef species would improve the robustness of future connectivity analysis. This could be achieved after synthesizing databases and independent guild-specific studies on larval traits (Fisher et al, 2005;Macpherson and Raventós, 2006;Luiz et al, 2013;Green et al, 2015;Gumanao et al, 2016;Madin et al, 2016;Baird et al, 2021) and contextualizing these to the species found in the Philippine coral reefs.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, expanding the representation of coral reef species would improve the robustness of future connectivity analysis. This could be achieved after synthesizing databases and independent guild-specific studies on larval traits (Fisher et al, 2005;Macpherson and Raventós, 2006;Luiz et al, 2013;Green et al, 2015;Gumanao et al, 2016;Madin et al, 2016;Baird et al, 2021) and contextualizing these to the species found in the Philippine coral reefs.…”
Section: Discussionmentioning
confidence: 99%
“…The reef-building coral Acropora digitifera , was used as a model for SB as it is widely distributed and abundant on shallow reefs throughout the Indo-West Pacific. Its digitate morphology facilitates fragment removal for conducting stress assays, and spawning times are well established for many locations (Keith et al, 2016; Baird et al, 2021). All of the work described here was carried out at the Palau International Coral Reef Center (PICRC) in the Republic of Palau located in Western Pacific Ocean (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Several advances have been made to improve the practices associated with CLP in recent years. The modes of sexual reproduction for approximately half of extant species of hermatypic scleractinians have been identified (Baird et al, 2009) and the timing of spawning catalogued for >300 Indo-Pacific coral species (Baird et al, 2021). CLP has been successfully executed in different geographical regions with different species under ex situ and in situ conditions (Omori, 2019; Randall et al, 2020) with sexually propagated colonies that were outplanted to the reef reaching sexual maturity (Nakamura et al, 2011; Baria et al, 2012; Guest et al, 2014; Chamberland et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The reef-building coral A. digitifera, was used as a model for SB as it is widely distributed and abundant on shallow reefs throughout the Indo-West Pacific. Its digitate morphology facilitates fragment removal for conducting stress assays, and spawning times are established for many locations (Keith et al, 2016;Baird et al, 2021). All of the work described here was carried out at the Palau International Coral Reef Center (PICRC) in the Republic of Palau located in Western Pacific Ocean (Supplementary Material 1A).…”
Section: Selection Of Parental Colonies For Selective Breedingmentioning
confidence: 99%
“…Several advances have been made to improve the practices associated with CLP in recent years. The modes of sexual reproduction for approximately half of extant species of hermatypic scleractinians have been identified (Baird et al, 2009) and the timing of spawning cataloged for >300 Indo-Pacific coral species (Baird et al, 2021). CLP has been successfully executed in different geographical regions with several species under ex situ and in situ conditions (Omori, 2019;Randall et al, 2020) with sexually propagated colonies that were outplanted to the reef reaching sexual maturity (Nakamura et al, 2011;Baria et al, 2012;Guest et al, 2014;Chamberland et al, 2016).…”
Section: Introductionmentioning
confidence: 99%